Genetic Factors of Campylobacter jejuni Required for Its Interactions with Free-Living Amoeba - Deepti Pranay Samarth; Asim Z. Abbasi; Young Min Kwon (Pathogens)
Acanthamoeba, a free-living amoeba ubiquitous in environmental water, has been considered as the environmental reservoir of certain bacterial pathogens, including Campylobacter jejuni, an intracellular human pathogen causing self-limiting gastroenteritis. Acanthamoeba-C. jejuni interaction mechanisms may help clarify how the otherwise fastidious bacterium C. jejuni survives in environmental waters. In this study, we constructed single deletion mutants of C. jejuni strain 81–176 for the 10 selected genes (motAB, ciaB, kpsE, virB11, cheY, flaAB, cstII, docB, sodB, and cadF) previously shown to be important for the interaction (invasion and intracellular survival) of C. jejuni with mammalian hosts. We used a modified gentamicin protection assay to quantify the internalization and intracellular survival of these mutants and the wild type with the two species of Acanthamoeba (A. castellanii and A. polyphaga). Both internalization and intracellular survival were significantly lower for all mutants compared to the wild type with both amoeba strains, except for ΔcstII in the internalization assay with A. castellanii (p < 0.05). The results of this study highlight that the mechanisms used by C. jejuni to interact with mammalian hosts are conserved in its interactions with amoeba hosts. This understanding may be useful in developing effective strategies to reduce the transmission of C. jejuni to chickens through drinking water.